Valor nutricional e características fermentativas da silagem de capim-mombaça com adição de farelo de girassol - Costa, Eduardo Rodolfo da (2015)
The nutritional value and fermentative characteristics of the silage grass mombaça with sunflower meal inclusion were evaluated. The treatments consisted of four levels of inclusion: 0%, 10%, 15% and 20%. The levels of dry matter determined in silage grass mombaça, differed depending on the sunflower meal inclusion levels, ranging from 24.69 % to 28.50%. The CP content ranged from 11.63 % to 21.651 % and significant differences were observed between the inclusion levels (P<0.05). The highest level of sunflower meal inclusion - 20% - resulted in smaller losses by effluent. The pH values found varied between 4.89 and 5.57. The average levels of ammonia nitrogen (NH3-N) remained between 1.33 and 6.42. The average levels of residual soluble carbohydrates ranged between 4.63 and 8.38, with significant similarity only between the levels of 15% and 20 % of sunflower meal (P> 0.05). The contents of lactic acid, acetic, propionic and butyric ranged from the 1,245 to 3,898; the 2.428 to 8.670; the 0.248 to 0.135 and the 0.016 to 0.027 respectively, and differed significantly (P<0.05) between the sunflower meal levels. The degradability of the dry matter of silage varied as a function of sunflower meal inclusion levels , having the potential degradability (PD) between 71.46 % and 81.96 %, being to 27.86 % to 32.83 % variation to the fraction "a" and between 39.01 % and 52.07 % for the "b" fraction . Regarding the CP, PD ranged from 83.09 % to 92.57 %, and the contents of the fraction "a", fractions "b" and part "c", were significantly influenced by the addition levels sunflower meal (P < 0.05) showing variation of 24.79 % to 61.50 %, 28.68 % to 59.73 %, and 0.0194 % to 0.0411 %, respectively.